2013
DOI: 10.1371/journal.pone.0065738
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility and Favorable Response of Mesenchymal Stem Cells on Fibronectin-Gold Nanocomposites

Abstract: A simple surface modification method, comprising of a thin coating with gold nanoparticles (AuNPs) and fibronectin (FN), was developed to improve the biocompatibility required for cardiovascular devices. The nanocomposites from FN and AuNPs (FN-Au) were characterized by the atomic force microscopy (AFM), UV-Vis spectrophotometry (UV-Vis), and Fourier transform infrared spectroscopy (FTIR). The biocompatibility of the nanocomposites was evaluated by the response of monocytes and platelets to the material surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 49 publications
(50 reference statements)
1
50
0
Order By: Relevance
“…Additionally, AN (15 nm) was found to be efficient in inhibiting HePG2-CM-induced proliferation and migration of epithelial cells through the downregulation of vascular endothelial growth factor (VEGF) after incubation of human umbilical vein endothelial cells in HePG2-CM medium. 40 In the present study, we demonstrated that the AN-LP nanoemulsion relative to the LP only treatment exhibited a higher suppressive effect in the migration of the EMT markers of HT-29 cells, as evident by the enhanced expression of E-cadherin and the decreased expressions of Akt and NFkB. Nonetheless, the detailed mechanism of the AN-LP nanoemulsion in inhibiting the migration of cancer cells needs to be further explored.…”
Section: Migration Of Ht-29 Cellsmentioning
confidence: 57%
See 1 more Smart Citation
“…Additionally, AN (15 nm) was found to be efficient in inhibiting HePG2-CM-induced proliferation and migration of epithelial cells through the downregulation of vascular endothelial growth factor (VEGF) after incubation of human umbilical vein endothelial cells in HePG2-CM medium. 40 In the present study, we demonstrated that the AN-LP nanoemulsion relative to the LP only treatment exhibited a higher suppressive effect in the migration of the EMT markers of HT-29 cells, as evident by the enhanced expression of E-cadherin and the decreased expressions of Akt and NFkB. Nonetheless, the detailed mechanism of the AN-LP nanoemulsion in inhibiting the migration of cancer cells needs to be further explored.…”
Section: Migration Of Ht-29 Cellsmentioning
confidence: 57%
“…In addition, LP was shown to be effective in inhibiting tumor growth and progression in a mouse xenograft model of colon cancer, with the inhibition being inversely proportional to the MMP-9 concentration in mouse blood. 39 The response of mesenchymal stem cells toward fibronectin-gold nanocomposites was studied by Hung et al, 40 illustrating that this treatment could enhance cell proliferation, decrease reactive oxygen species production, and increase expressions of MMP-9 and endothelial nitric oxide synthase which, in turn, affected the migration of human umbilical mesenchymal stem cells. Additionally, AN (15 nm) was found to be efficient in inhibiting HePG2-CM-induced proliferation and migration of epithelial cells through the downregulation of vascular endothelial growth factor (VEGF) after incubation of human umbilical vein endothelial cells in HePG2-CM medium.…”
Section: Migration Of Ht-29 Cellsmentioning
confidence: 99%
“…Reduction in cellular ROS due to AuNP has been shown to be concentration dependent [22]. Similar to the effects of proliferation and migration, the concentration and size of the nanoparticle affects how the cells interact with the particles [39]. Previous studies of cellular ROS concentrations on collagen-100 nm AuNP constructs have shown a concentration dependent decrease in ROS production [16].…”
Section: Discussionmentioning
confidence: 97%
“…42 Hung et al investigated the biocompatibility of bronectin coated gold nanoparticles (FNAuNP) with mesenchymal stem cells. 43 They found the biocompatibility of the FN-AuNP's compared favorably to pure bronectin. Fendyur and Spira were able to culture rat derived cardiomyocytes on laminin coated gold electrodes.…”
Section: Platinum Coating Of Gelmentioning
confidence: 99%